Apelin-13 Suppresses Neuroinflammation Against Cognitive Deficit in a Streptozotocin-Induced Rat Model of Alzheimer’s Disease Through Activation of BDNF-TrkB Signaling Pathway - Luo, Huaiqing; Xiang, Yang; Qu, Xiangping; Liu, Huijun; Liu, Chi; Li, Guangyi; Han, Li; Qin, Xiaoqun (Frontiers in Pharmacology, 2019)
Alzheimer' disease (AD), a progressive neurodegenerative disease characterized by impairments of cognitive function, is associated with inflammation which is suggested to be a potential cause of synaptic deficits and neuronal loss. Apelin-13, a predominant neuropeptide with inhibiting effect on inflammation, has beneficial effects on cognition memory and neuronal damage. However, whether apelin-13 can protect neurons to ameliorate cognitive deficits of AD by inhibiting inflammatory response and the underling mechanism remains largely unknown. To test this hypothesis, rats were intracerebroventricularly (ICV) injected with streptozotocin (3mg/kg) alone or in combination with apelin-13 (2μg). And tropomyosin receptor kinase B (TrkB) blocker K252a (200 nM) was administrated 10 min before apelin injection. Futhermore, cognitive performance was assessed by new object recognition (NOR) and Y-maze tests. Protein expression of apelin, APJ, microglial marker (IBA1), astroglia marker (GFAP), interleukin 1 beta (IL-1β), tumor necrosis factor-α (TNF-α), synaptophysin (SYP), brain-derived neurotrophic factor (BDNF), TrkB in the hippocampus were examined by western blotting or immunohistochemistry. And the gene expression of IBA1, GFAP, IL-1β, TNF-α and SYP were detected by real-time quantitative polymerase chain reaction (PCR). Inflammatory disorder in the hippocampus was tested by hematoxylin and eosin (H&E) staining. We observed that apelin/APJ signaling in the hippocampus is downregulated in a STZ-induced rat model of AD. Apelin-13 was found to significantly ameliorated STZ-induced AD-like phenotypes including congnitive deficit and the damage of neuron and synaptic plasticity. Moreover, apelin-13 inhibited microglia and astrocyte activation, reduced IL-1β and TNF-α expression and hippocampal BDNF/TrkB expression deficit in AD rats. Finally, apelin-13-mediated effects were blocked by TrkB receptor antagonist K252a. These results suggest that apelin-13 upregulates BDNF/TrkB pathway against cognitive deficit in a STZ-induced rat model of AD by attenuating glial activation and the expression of inflammatory factors.